2017
DOI: 10.1007/s12032-017-1050-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness comparison between neoadjuvant chemohormonal therapy and extended pelvic lymph node dissection in high-risk prostate cancer patients treated with radical prostatectomy: a multi-institutional analysis

Abstract: The aim of the present study was to assess the cost-effectiveness of extended pelvic lymph node dissection (ePLND) compared to neoadjuvant chemohormonal therapy using gonadotropin-releasing hormone agonist/antagonist and estramustine. We retrospectively analyzed data within Michinoku Urological Cancer Study Group database containing 2971 PC patients treated with radical prostatectomy (RP) at four institutes between July 1996 and July 2017. We identified 237 and 403 high-risk patients who underwent RP and ePLND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For high-risk patients (IV, age ≥ 75 years, comorbidity) with ovarian cancer, NAC was cost-effective with higher QALY and similar cost, with the opposite result for patients who are not high risk. 28 In prostate cancer, 34 NAC was the dominant strategy in high-risk patients (clinical stage T2c or T3, initial prostatespeci c antigen levels ≥ 20 ng/mL, biopsy Gleason score (GS) ≥ 8 according to the D'Amico risk strati cation system). 40 Patient numbers at various stages (Table S 4 in the Supplement), revealed NAC as dominant among majority of patients at stage IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For high-risk patients (IV, age ≥ 75 years, comorbidity) with ovarian cancer, NAC was cost-effective with higher QALY and similar cost, with the opposite result for patients who are not high risk. 28 In prostate cancer, 34 NAC was the dominant strategy in high-risk patients (clinical stage T2c or T3, initial prostatespeci c antigen levels ≥ 20 ng/mL, biopsy Gleason score (GS) ≥ 8 according to the D'Amico risk strati cation system). 40 Patient numbers at various stages (Table S 4 in the Supplement), revealed NAC as dominant among majority of patients at stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…study retrospectively analyzed the cost-effectiveness of NAC and AC in high-risk patients with prostate cancer. 34 The cost of AC was $4,174 higher than that of NAC. The 5-year biochemical recurrence-free rates of AC and NAC were 59% and 86%, respectively.…”
Section: Prostate Cancermentioning
confidence: 99%
“…In our study, the median number of resected lymph nodes was 10 (range: 2–28; Table 1 ). A previous study showed that the number of resected lymph nodes by ePLND was significantly higher than that of limited PLND (median: 6 (range: 2–9), 16 (range: 13–21), respectively) [ 23 ]. By ePLND, resection of a greater number of metastatic lymph nodes might lead to improved oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures of RARP and standard pelvic lymph node dissection were performed using the basic technique described previously. 21 , 22 Extended pelvic lymph node dissection was not performed in this study. The exclusion criteria were as follows: (1) patients who could not be evaluated for frailty and postoperative pain and (2) those treated with open radical prostatectomy.…”
Section: Methodsmentioning
confidence: 99%